Marine octopus: global distribution, extraction methods, bioactive biomaterials, and biomedical applications - Mengfei Li; Mengfei Li; Mengfei Li; Zhihong Deng; Kun Cheng; Kun Cheng; Kun Cheng; Xianjun Fu; Xianjun Fu; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science)
Octopus, an abundant marine species with diverse applications, is attracting growing attention for its unique biological characteristics and potential utilization in food science and biotechnology. Octopus contain amino acids, active peptides, fatty acids and trace elements and these bioactives exhibit a wide range of effects, including anti-bacterial, anti-tumor, antioxidant and anti-aging activities. The structure of octopus arm and suckers provides biomimetic design inspiration for tissue engineering and the regenerative ability of octopus provides reference for research in biomedical material. Therefore, this review systematically summarizes the research progress on octopus resource distribution, extraction methods, nutrients, bioactive compounds substances and research on regeneration material, aiming to promote the development and utilization of octopus resources. Firstly, the extractions methods of octopus were systematically reviewed. Secondly, seven kinds of nutrients concluded were introduced to reveal the nutritional components of octopus. Finally, the application of octopus in biotechnology and the research progress on their regenerative ability were summarized. This review provides a basis and reference for octopus functional nutrients and application of octopus biomedical materials.